Scorpion-Induced Acute Coronary Syndrome: A Stinging Complication - Arun Katwaroo MBBS; Kristianne Austin MBBS; Alexandria Bharat MBBS; Varun Chatoo MBBS; Priya Ramcharan MBBS, MRCP; Valmiki Seecheran MBBS, MSc; Rajeev Seecheran MBBS, MHA; Stanley Giddings MBBS, FRCP (E); Naveen Anand Seecheran MBBS (MD) (SAGE Publishing, 2024)
The Tityus trinitatis , a black scorpion species endemic to the fauna of Trinidad, has been implicated in envenomation with devastating clinical sequelae such as acute pancreatitis and major adverse cardiovascular events. We present the first in-Caribbean case of a 59-year-old Caribbean South Asian male with human immunodeficiency virus who presented with a non-ST-segment-elevation acute coronary syndrome after being stung, which was managed with comprehensive, guideline-directed medical therapy. The clinician should be cognizant of scorpion-induced acute coronary syndrome (ACS) as a potential sequela of envenomation and its clinical management.